Pengaruh Employer Branding dan Media Sosial Terhadap Reputasi Perusahaan dan Niat Melamar pada PT Prima Indah Lestari di Era Digital - Mega, Mega; Heni Susilowati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the influence of employer branding and social media on job application intention, with corporate reputation serving as a mediating variable at PT Prima Indah Lestari in the digital era. A quantitative explanatory approach with a causal research design was employed. Data were collected from 96 prospective employees selected through purposive sampling using a questionnaire. The data were analyzed using IBM SPSS Statistics, applying multiple linear regression analysis and the Sobel test. The findings indicate that employer branding, social media, and corporate reputation positively and significantly affect job application intention, both partially and simultaneously. Furthermore, the results confirm that corporate reputation significantly mediates the relationship between employer branding and social media on job application intention.